[International Women's Day March] - Ford, Sue, 1943-2009. (1988)
Collection of photographs of an International Women's Day march, held in Sydney, 1988. Photographs depict mostly crowd scenes.
Condition: good.
Title devised by cataloguer based on information from acquisition file 204/07/00064.
Keywords: Women -- New South Wales -- Sydney -- Photographs; Parades -- New South Wales -- Sydney -- Photographs; International Women's Day -- New South Wales -- Sydney -- Photographs